SEMARANG CITY GOVERNMENT EFFORT AND BATIK ARTISANS PARTICIPATION IN MSMEs OF BATIK CRAFTS EMPOWERING (STUDY IN COORPORATIVES AND MSMEs DEPARTMENT OF SEMARANG CITY AND REJOMULYO BATIK VILLAGE SEMARANG CITY) - Sholachuddin, Hanif; Priyadi, Budi Puspo (Journal of Public Policy and Management Review, 2019)
Semarang city has a strategic role in empowering MSMEs, one of which is the MSMEs of Semarangan Batik crafts. However, it has not been able to develop and still has some problems. The purpose of this study is to determine the efforts made by Coorporatives and MSMEs Department of Semarang city, the participation of batik artisans, and its constrains. The research is qualitative descriptive research. The results show that the efforts made by Coorporative and MSMEs Department of Semarang city are good enough based on aspects of human resource development, community capital fertilization, productive bussiness development and the provision of appropriate information, while the participation of batik artisans in empowering of batik crafts in Rejomulyo Batik village has been good based on aspects of participations in decision making, participation in the implementation of activities, participation in monitoring and evaluation in the utilitation of development results. Nevertheless, the obstacles encountered in Rejomulyo Batik village is lack of facilities and infrastructure, difficulties in finding workforce, and less active basic community. For this reason, suggestions that can be given are Coorporatives and MSMEs Department of Semarang need to make and hold website training, put up banners and make news in print and electronic media, must coordinate with several institutions and conduct Corporate Social Responsibility (CSR) related to batik training , it is necessary to improve the monitoring function of the community,, while the batik artisans themselves must be able to utilize the internet and social media for the promotion of batik products, it must be more responsive and enthusiastic to increase public awareness, especially the younger generation and must be more frequent and intense in conducting socialization and batik activities through the community.